Talker-Specific Generalization of Pragmatic Inferences based on Under- and Over-Informative Prenominal Adjective Use - Pogue, Amanda; Kurumada, Chigusa; Tanenhaus, Michael K. (Frontiers in Psychology, 2016)
According to Grice’s (1975) Maxim of Quantity, rational talkers formulate their utterances to be as economical as possible while conveying all necessary information. Naturally produced referential expressions, however, often contain more or less information than what is predicted to be optimal given a rational speaker model. How do listeners cope with these variations in the linguistic input? We argue that listeners navigate the variability in referential resolution by calibrating their expectations for the amount of linguistic signal to be expended for a certain meaning and by doing so in a context- or a talker-specific manner. Focusing on talker-specificity, we present four experiments. We first establish that speakers will generalize information from a single pair of adjectives to unseen adjectives in a speaker-specific manner (Experiment 1). Initially focusing on exposure to underspecified utterances, Experiment 2 examines: a) the dimension of generalization; b) effects of the strength of the evidence (implicit or explicit); and c) individual differences in dimensions of generalization. Experiments 3 and 4 ask parallel questions for exposure to over-specified utterances, where we predict more conservative generalization because, in spontaneous utterances, talkers are more likely to over-modify than under-modify.